Effect of the ring current on preconditioning the magnetosphere for steady magnetospheric convection. Issue 10 (30th May 2013) - Juusola, L.; Partamies, N.; Tanskanen, E.
<x xml:space="preserve">Abstract</x> [1] Steady magnetospheric convection (SMC) occurs when reconnection rates on the dayside and in the distant tail are balanced. An enhanced ring current could support this, by stabilizing the tail against near‐Earth reconnection and by facilitating the prompt return of magnetic flux to the dayside. We use 32 years of magnetic index and solar wind data to study the effect of the ring current on preconditioning Earth's magnetosphere for SMC. The ring current is found to be enhanced during SMCs. Solar wind driving is similar but the ring current is weaker before the SMC, and the ring current is similar but solar wind driving is either weaker or stronger after the SMC than during it. This indicates that the magnetosphere cannot enter the SMC mode until the ring current has enhanced sufficiently for the prevailing driving conditions, and that when the driving exceeds a certain level, the ring current stabilization will fail.